Potenciais legais e ambientais de uma área para loteamento residencial: obstáculos e oportunidades - Santos, Luiz Fernando dos (Universidade Federal de São Carlos, 2022)
With the accelerated urbanization and the effects of the Industrial Revolution, the anthropic actions on the environment have had their deleterious effects increased due to the imbalance between population, environmental resources, and pollution. The terrestrial, aquatic, and atmospheric environments suffer adverse impacts generated by human activities that must be avoided or mitigated. Land use and occupation must be preceded by Environmental and Urban Planning, which ultimately aims to balance the environment, society and the economy in an arrangement known as the triple bottom line (3BL). It is in this context that the proposed work is inserted, having as its objective to analyze whether there is legal and environmental potential for the realization of an adequate environmental and urban planning in an area destined for the construction of a residential subdivision. To this end, research was conducted on all legislation of interest - environmental and urban planning - in order to verify whether its application can generate positive and lasting results throughout the area studied, its surroundings and its area of influence. The present work was carried out while following the development of a Feasibility Study that aimed at implementing a residential subdivision in a certain area, considering that the lack of adequate Urban Planning affects the environmental quality, causing problems of various kinds, such as public health, urban spatial planning and natural ecosystems. Thus, from the case study proposed by Feasibility Study, the effectiveness of the Principles of Environmental Legislation is confronted at all times in order to achieve the highest goal: environmental sustainability.
Legal and environmental potentials of an area for residential subdivision: obstacles and opportunities
Keywords: Planejamento ambiental e urbano; Uso e ocupação de solo; Zoneamento geoambiental; Environmental and urban planning; Land use and occupation; Geoenvironmental zoning; OUTROS